Analisis Pengaruh Toko Ritel Modern Terhadap Pendapatan Pedagang Tradisional dalam Perspektif Ekonomi Islam - Andi Triyawan (Falah: Jurnal Ekonomi Syariah, 2018)
The aim of this research isto find out the influence of retail modern existence through traditional retail seller income at Subdistrict Ngawi Regency Ngawi and discover its solution in islamic economic. And giving some sugestion for retial traditional seller to evolving their business. This research is quantitativefield research, by obtaining primary source from questioner which had devided to traditional retail seller in subdistric Ngawi. The result is showing that, Sig in Coefficient table are about 0,433>0,05 which tell that Ho is rejected, which mean is, there is some effect between the existence of modern retailwith traditional retail seller income in subdistrict Ngawi. And with T-Test also showed that Ho is rejectedwith t-count<t table (-0,031<2,093). Then, we can conclude regresion equation Y’ = 4,539 - 0,031X + e, which means, if the exixtence of modern retail is valued 0, then the income of traditional retail seller is valued 4,539. Because of regresion coefficient the existence of modern retail is about -0,031, then every additional one unit of modern retail will affect to decrease of traditional retail seller income about Rp 0,031.